Structural behaviour and design of cold-formed austenitic stainless steel flat-oval hollow section beam-columns - Li, Shuai (2024)
This paper presents experimental and numerical investigations into the global buckling behaviour and resistances of cold-formed austenitic stainless steel flat-oval hollow section beam-columns under combined compression and bending. A testing programme, including initial geometric imperfection measurements and ten beam-column tests about the cross-section major and minor principal axes, was firstly conducted. The key obtained test results, including failure loads, load–deformation histories and failure modes, were reported. Following the testing programme, a numerical modelling programme was performed, with finite element models developed to simulate the beam-column test results and then used to conduct parametric studies for generating additional numerical data. Then, the applicability of relevant codified design interaction curves to cold-formed austenitic stainless steel flat-oval hollow section beam-columns was evaluated based on the test and numerical data. The evaluation results revealed that the design interaction curve of the American specification resulted in an overall good level of design accuracy and consistency, while the design interaction curve of the European code led to slightly conservative resistance predictions, mainly due to the conservative bending end point. To address this shortcoming, a revised Eurocode design interaction curve with an improved bending end point was proposed and shown to provide more accurate resistance predictions for cold-formed austenitic stainless steel flat-oval hollow section beam-columns than the original Eurocode design interaction curve.